Endocrinopathies in HIV Infected Patients / Rosdina Zamrud Ahmad Akbar ... [et al.] - Ahmad Akbar, Rosdina Zamrud; Wan Muhammad Hatta, Sharifah Faradila; Mohd Noh, Rosnida; Mohd Shah, Fatimah Zaherah; Abdul Rahman, Thuhairah; Abdul Ghani, Rohana; Ismail, Zaliha (Universiti Teknologi MARA Cawangan Selangor, 2020)
Introduction: Hormonal abnormality is one of many clinical manifestations of HIV infections that is not well understood. However, the consequences could affect quality of life and are potentially treatable. Thus, this study aimed to determine the prevalence and associated factors of thyroid, adrenal and gonadal dysfunctions among HIV-infected patients. Methods: This is a single centre cross-sectional study involving 150 HIV-infected patients attending the HIV clinic. Each subject was required to answer specific symptoms questionnaire and their medical records were reviewed for relevant clinical and biochemical data. Blood for was collected and thyroid hormones, cortisol, ACTH, FSH, LH, testosterone and estradiol were analysed using electrochemiluminescent immunoassay. Thyroid, adrenal and gonadal axes abnormalities were identified. Results: Hypogonadism had the highest prevalence amongst the endocrine abnormalities, which was detected in 23 patients (15.3%), followed by thyroid dysfunction in 18 patients (12%) and hypocortisolism in 2 patients (1.3%). There was significant correlation between CD4 count, BMI and age with the hormone levels. Conclusion: Prevalence of endocrine abnormalities was low in these well-treated HIV-positive patients, with hypogonadism being the most common. However, significant correlations between CD4 count, age and BMI with the hormonal levels were detected. Clinical symptoms in relation to endocrinopathy are not specific as a screening tool thus underscoring the need for biochemical tests to identify these treatable conditions.